2007
DOI: 10.4049/jimmunol.178.6.3688
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA Expression of IL-8, FOXP3, and IL-12β Differentiates Latent Tuberculosis Infection from Disease

Abstract: Differentiation of active from latent tuberculosis (TB) is a major challenge in the control of TB. In this study, PBMC from latent TB-infected subjects, TB patients, and tuberculin skin test-negative donors stimulated with the Mycobacterium tuberculosis (Mtb)-specific Ag, early secretory antigenic target 6, and mRNA for 45 immune-related genes was measured by quantitative real-time PCR. Univariate analysis showed significant differences in the expression of 10 genes (IFN-γ, FOXP3, IL-1α, IL-1β, IL-2, IL-6, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 26 publications
6
50
1
2
Order By: Relevance
“…For example, the shift from dominance of T cells secreting only IFN-␥ toward codominance of antigen-specific CD4 ϩ T cells secreting IL-2 and IL-2 plus IFN-␥-during treatment of active disease (29) suggests that a dual cytokine signature may correlate better with antigen load than measurement of only one cytokine. Indeed, one recent study suggested that simultaneous measurement of transcription of six cytokines by real-time reverse transcription-PCR may distinguish between active TB infection and LTBI, although the study sample size was small (42). Given that RD1-specific IFN-␥-secreting T cells correlate better with pathology than with protective immunity, measuring cytokine secretion profiles of RD1 antigen-specific T cells may in the future enable accurate discrimination of active infection from latent infection.…”
Section: Figmentioning
confidence: 99%
“…For example, the shift from dominance of T cells secreting only IFN-␥ toward codominance of antigen-specific CD4 ϩ T cells secreting IL-2 and IL-2 plus IFN-␥-during treatment of active disease (29) suggests that a dual cytokine signature may correlate better with antigen load than measurement of only one cytokine. Indeed, one recent study suggested that simultaneous measurement of transcription of six cytokines by real-time reverse transcription-PCR may distinguish between active TB infection and LTBI, although the study sample size was small (42). Given that RD1-specific IFN-␥-secreting T cells correlate better with pathology than with protective immunity, measuring cytokine secretion profiles of RD1 antigen-specific T cells may in the future enable accurate discrimination of active infection from latent infection.…”
Section: Figmentioning
confidence: 99%
“…In this study, PTB patients and PTB HHC have not shown any significant difference during their follow up. IL-1β expression up-regulated in the alveolar macrophages of TB patients in a Chinese study and was significantly low in ESAT-6 stimulated PBMC of PTB patients when compared to the LTBI individuals, however statistical significance was not observed with respect to healthy controls [32,33]. IL-1β expression was low in the DM compared to HCs, which was contrary to a study where increased IL-1β mRNA was examined in the beta cells of DM patients with minimal or no expression [34].…”
Section: Discussionmentioning
confidence: 83%
“…A recent meta-analysis suggested that IGRAs do not have high predictive value for development of active tuberculosis ( (Rangaka et al, 2011) and concluded that the identification of better predictive markers was essential. Promising results have been reported in this regard with the use of poly-cytokine bio-signatures (Chegou et al, 2009) and measurement of expression levels of mRNA transcripts for IL-8, FOXp3 and IL-12  in ESAT-6 stimulated polymorphonuclear cells (Wu et al, 2007). T cells secreting only TNF have recently been proposed as indicators for active TB (Harari et al, 2011).…”
Section: Biomarkersmentioning
confidence: 99%